The Effects of Oleuropein and Vitamin C on Diabetic Nephropathy Induced by Streptozotocin (STZ) In Male Rats - Marium Hussein (AlQalam Journal of Medical and Applied Sciences, 2021)
Aims. In the present study, we aimed to examine the efficacy of oleuropein and vitamin C in reducing the metabolic abnormalities kidney function accompanied to streptozotocin-induced diabetes in male albino rats. The antioxidants, such as phenolic compound oleuropein and Vitamin C play important roles in improve cell function and protect the affected tissues. Methods. The present work was designed to study the effects of oleuropein and vitamin C of diabetic nephropathy in male rats. Diabetes was induced by a single i.p. dose of STZ (40 mg/kg b.w.). Pure oleuropein compound (5 mg/kg b.w.) and vit.C (150 mg/kg b.w.) was orally administered once per a day for 15 days after diabetes induction. Results. Oleuropein and Vitamin C have been observed to keep creatinine, urea, uric acid and kidney function near normal levels compared to very high levels in the diabetic group, and improvement total protein globulin and albumin. Conclusion. Oleuropein and vitamin C significantly attenuated the oxidative status of diabetic rats. In addition, improved the different changes kidney tissue in diabetic rats treated with oleuropein and vitamin C compared with diabetic rat.